Three Paleocoastal Lithic Sites on Santa Cruz Island, California. (2nd January 2016) - Erlandson, Jon M.; Gill, Kristina M.; Glassow, Michael A.; Gusick, Amy E.
Abstract : Paleocoastal sites, dated between ∼13, 000 and 8000 cal yr BP, are relatively abundant on California's Northern Channel Islands but rare on the largest island of Santa Cruz. Here we describe three lithic sites containing chipped-stone crescents and, in one case, a stemmed Channel Island Barbed point fragment. Elsewhere on the islands, datable sites containing crescents are either terminal Pleistocene or early Holocene in age. Two of the lithic sites produced no datable organic remains, but one contains a small patch of intact shell midden dated to ∼8650 cal yr BP. These three sites add to the growing number of Paleocoastal sites on Santa Cruz and the other Northern Channel Islands.